Percepção do enfermeiro acerca da readaptação funcional do trabalhador da enfermagem sob a ótica da gestão - Gracióli, Jocelaine Cardoso (2017)
This study aimed mainly to know the nurses perceptions on the Nursing workers functional readaptation in a teaching hospital. The specific goals were to know the nurses` strategies on receiving the Nursing worker in functional readaptation and to describe the appraisal process of the nurse`s accomplished performances with the Nursing worker in functional readaptation in a teaching hospital. The methodology consisted in a exploratory descriptive field research with a qualitative approach and it happened in Santa Maria`s University Hospital. The participants were 19 nurses under the Brazilian legal labor system for public organizations who work with Nursing workers in the functional readaptation process. The data collection was done through semi structured interviews between May and June, 2016. The data were analyzed according to Minayo`s operative proposal for content analysis. All the ethical aspects were respected in accordance to the December, 2012 Brazilian National Health Counsil resolution number 466 and the project was approved under the number CAAE 53557916.4.0000.5346. This dissertation includes three articles. The first targeted to discuss the main goal and it comprehends the following content categories: nurse`s perception about the readjusted worker; the easiness and difficulties of the return to work; the reception of the worker in functional readaptation returning to work. The second aimed to know the nurses` strategies on receiving the Nursing worker in functional readaptation with the categories: user embracement and worker in functional readaptation care at the work setting; planning of the readjustment process for the Nursing worker. Lastly, the third article intended to describe the appraisal process of the nurse`s accomplished performances with the Nursing worker in functional readaptation in a teaching hospital setting. Communication, one of the ranked strategies, was one of the maneuvers used by the nurse while appraising and informally evaluating. The main results according to the perception of the interviewed nurses are: the discrimination and prejudice faced by workers in functional readaptation; insecurity about returning to work, an aspect that affects their performance; the necessity for willingness to return to work, and the nurses also pointed out management difficulties to work with this worker and the importance of institutional planning to receive the nursing worker in the process of functional readaptation. As strategies to receive this worker, the nurses emphasized the user embracement, the negotiation, the communication process and respect to the labor limitations. Regarding the performance appraisal, participating nurses advocated for daily evaluations, based on communication and on the adoption of an informal method of appraisal. It is expected for this study to contribute to the return of nursing workers to work when in a situation of health restriction, and that it also can enable managers to devise strategies that allow a healthy functional readaptation permeated by positive experiences for workers, managers and institutions. In addition, it hopes to stimulate reflections and discussions within academic and professional settings, encouraging new researches about this subject. Thus, it is possible to conclude that the nursing workers` process of functional readaptation is a complex one, requiring the institution involvement, the management staff and the worker itself. Developing a team work, so that they accommodate the worker returning to labor activities, facilitates the readptation. Another attitude that contributes to the worker`s return to work is credited to a frank process of negotiation between the readjusted and the management staff. Furthermore, willingness and commitment to return to work is necessary on the worker`s behalf.